2016
DOI: 10.1371/journal.pbio.1002355
|View full text |Cite
|
Sign up to set email alerts
|

Interpreting the Dependence of Mutation Rates on Age and Time

Abstract: Mutations can originate from the chance misincorporation of nucleotides during DNA replication or from DNA lesions that arise between replication cycles and are not repaired correctly. We introduce a model that relates the source of mutations to their accumulation with cell divisions, providing a framework for understanding how mutation rates depend on sex, age, and cell division rate. We show that the accrual of mutations should track cell divisions not only when mutations are replicative in origin but also w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
166
2
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 126 publications
(179 citation statements)
references
References 52 publications
9
166
2
2
Order By: Relevance
“…(Because CGI are often hypomethylated, we remove these regions from this analysis, and, unless specified otherwise, refer to transitions at CpG sites outside of CGIs as "CpG transitions.") Mathematical modeling of different substitution mechanisms predicts that mutations that are nonreplicative in origin and highly inefficiently repaired should depend on absolute time, rather than on the number of cell divisions, and hence should be more clocklike among species (21). In contrast, mutations that arise from replication errors, or are nonreplicative in origin but well repaired, should depend on the generation time and other life history traits, and therefore their substitution rates could vary considerably across primates (21,33).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…(Because CGI are often hypomethylated, we remove these regions from this analysis, and, unless specified otherwise, refer to transitions at CpG sites outside of CGIs as "CpG transitions.") Mathematical modeling of different substitution mechanisms predicts that mutations that are nonreplicative in origin and highly inefficiently repaired should depend on absolute time, rather than on the number of cell divisions, and hence should be more clocklike among species (21). In contrast, mutations that arise from replication errors, or are nonreplicative in origin but well repaired, should depend on the generation time and other life history traits, and therefore their substitution rates could vary considerably across primates (21,33).…”
Section: Resultsmentioning
confidence: 99%
“…Mathematical modeling of different substitution mechanisms predicts that mutations that are nonreplicative in origin and highly inefficiently repaired should depend on absolute time, rather than on the number of cell divisions, and hence should be more clocklike among species (21). In contrast, mutations that arise from replication errors, or are nonreplicative in origin but well repaired, should depend on the generation time and other life history traits, and therefore their substitution rates could vary considerably across primates (21,33). Thus, a priori, we expect CpG transitions outside CGI to be more clocklike than other types of substitutions (assuming similar rates of deamination across species).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…interaction between genetic diversity and the efficiency of selection that will tend to make the slope of the relationship between log(π N /π S ) and log(π S ) steeper. However, the importance of this effect remains unclear: although some studies have found evidence to suggest that there is a negative correlation between N e and μ (Piganeau and EyreWalker, 2009;Lynch, 2010;Cutter et al, 2013), the theory predicts a relatively small effect of N e on μ that could be masked by the impact of other influences on μ, such as rate of sperm production and exposure to mutagens (Gao et al, 2016). In addition, the theory suggests that the mutation rate of a species is reduced as far as possible by selection, with genetic drift preventing selection from further reducing the rate (Lynch, 2011).…”
Section: Discussionmentioning
confidence: 99%